Bahasa dan Worldview Menurut Syed Muhammad Naquib Al-Attas: Kritik atas Filsafat Bahasa Modern: Language and Worldview According to Syed Muhammad Naquib Al-Attas: A Critique on Modern Philosophy of Language - Moh Husnul Affan; M. Mukhtasar Syamsuddin (Center of Islamic and Occidental Studies, 2026)
Language is an instrument deeply embedded in human life due to its essential function and necessity. However, the significance of language becomes a crucial question when examined in relation to a particular social community or civilization. Contemporary philosophers of language have primarily focused their studies on reaching conclusions regarding the phenomenon of human linguistic activity. Syed Muhammad Naquib Al-Attas offered a renewed perspective on the study of language and its relationship with the worldview or nature view. Al-Attas developed his argument on the basis of human existence consisting of body and soul in one physical form. From this premise, Al-Attas argued that human beings possess a divine gift from God, namely language, as a means of expressing and conveying their thoughts. These thoughts are always connected to a particular system of thought, which is then referred to as a worldview. Al-Attas’s perspective on the relationship between language and worldview provides significant implications for contemporary linguistic studies. Therefore, this discourse is both important and relevant for further investigation. The arguments developed by Al-Attas offer a distinctive contribution to contemporary philosophy of language, distinguishing them from the approaches of many other philosophers. This study also aims to provide a critical reflection on contemporary philosophy of language, which is further discussed in the conclusion of this research.